Peran Krusial Farmakovigilans dalam Meningkatkan Keamanan Pasien (Patient Safety) - Ana Widyaningsih (PT Dexa Medica, 2025)
Pharmacovigilance is the science and activities related to the detection, assessment, understanding, and prevention of adverse drug effects or other drug-related problems. The importance of drug safety monitoring stemmed from the thalidomide tragedy, which led to the formation of international programs to strengthen the regulatory framework on drug safety. Drug safety evaluation is conducted through a series of testing stages before a drug is marketed. However, pharmacovigilance activities performed post-marketing are crucial for detecting rare side effects that could not be identified during the pre-marketing testing phases. Multisectoral collaboration among various relevant parties and stakeholders is vital for the success of pharmacovigilance, with the ultimate goal of ensuring the safe use of medicines and patient safety.